Customer Expectations and Performance of Banks : An Empirical Analysis - Panda, Rajesh; Swar, Biranchi Narayan (Indian Journal of Marketing, 2016)
The Indian banking industry is getting competitive day by day due to entry of new foreign banks and new licenses released by RBI for domestic players. Retail banking in India has evolved from offering mere deposits to a range of products and services. At the same time, different banks are creating various avenues like mobile banking, online banking, and so forth to enhance their respective customer experience. The customer base of these banks is different, and that's why they have different priorities in terms of service requirements. So, this paper tries to bring out various insights into the priority of customers for different services offered by different types of banks and thus help the banks to re-orient their strategy using the importance-performance analysis. Retail banks may use the approach followed in this study to improve their service level considering the priority of their customers. The findings could help the retail banks to identify the competitive dimensions within their organizations that are effectively-resourced, under-resourced, or over-resourced and re-align deployment of resources accordingly.